The Preservation Ecosystem of Toge Goreng: An Analysis of Tourist, Youth Generation, and Culinary Business Perspectives in Achieving the Sustainability of Bogor's Traditional Cuisine - Abi Saptadinata; Mita Purnamasari; Maryetti (The Postgraduate School of Tourism Sahid Polytechnic, 2025)
Purpose: This study aims to explore digital promotion strategies and presentation innovations as efforts to increase the interest of younger generations and tourists in toge goreng, a traditional dish from Bogor, and to support the preservation of local culinary heritage. Research method: The research adopts a descriptive qualitative approach using a case study strategy in several key culinary locations in Bogor, including Jalan Suryakencana, Pasar Ah Poong, and the area surrounding Bogor Botanical Gardens. Data were collected through in-depth interviews, participatory observation, semi-structured questionnaires, and documentation from social media and culinary articles. Thematic analysis was conducted with the aid of NVivo 15 to identify key patterns and themes. Data validity was ensured through triangulation of sources and methods, and adherence to ethical research principles. Results and discussion: Findings reveal that toge goreng is perceived as a symbol of local identity, yet its popularity among young consumers is declining due to modern food trends and limited online visibility. Despite the growing trend in gastronomic tourism, toge goreng lacks competitive appeal due to minimal innovation and promotion. However, opportunities exist in developing creative presentation techniques and leveraging digital platforms such as Instagram and TikTok. Cultural values remain a key element, and maintaining authenticity while modernizing the experience is essential. Collaboration among local vendors, tourism stakeholders, and content creators emerged as a strategic pathway to revitalize interest in toge goreng. Implications: This research underscores the need for a holistic and collaborative approach in preserving traditional foods like toge goreng. Practical implications include integrating digital marketing strategies, empowering local food entrepreneurs with training in visual branding, and fostering cross-sector partnerships. The study contributes to the discourse on cultural preservation in the context of modern food consumption and offers a replicable model for promoting other underappreciated traditional dishes within the broader scope of sustainable gastronomic tourism.